2019
DOI: 10.3389/fphar.2019.01200
|View full text |Cite|
|
Sign up to set email alerts
|

Genotype–Phenotype Association Analysis Reveals New Pathogenic Factors for Osteogenesis Imperfecta Disease

Abstract: Osteogenesis imperfecta (OI), mainly caused by structural abnormalities of type I collagen, is a hereditary rare disease characterized by increased bone fragility and reduced bone mass. Clinical manifestations of OI mostly include multiple repeated bone fractures, thin skin, blue sclera, hearing loss, cardiovascular and pulmonary system abnormalities, triangular face, dentinogenesis imperfecta (DI), and walking with assistance. Currently, 20 causative genes with 18 subtypes have been identified for OI, of them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 65 publications
(84 reference statements)
2
18
1
Order By: Relevance
“…lead to the synthesis of a reduced amount of normal type I collagen; the other is structural defect including missense mutation, mainly involving glycine replacement within Gly-Xaa-Yaa repeat. In the collagen triple helix, the Gly-substitution missense will produce structural deformation of the triple helix, leading to destabilization of the helical structure, affecting the synthesis of collagen [17][18][19][20]. In our study, the singlebase substitution in a Gly codon leading to Ala substitutions, c.1463G>C (p.G488A) (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…lead to the synthesis of a reduced amount of normal type I collagen; the other is structural defect including missense mutation, mainly involving glycine replacement within Gly-Xaa-Yaa repeat. In the collagen triple helix, the Gly-substitution missense will produce structural deformation of the triple helix, leading to destabilization of the helical structure, affecting the synthesis of collagen [17][18][19][20]. In our study, the singlebase substitution in a Gly codon leading to Ala substitutions, c.1463G>C (p.G488A) (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Type I collagen is the most abundant tooth matrix protein and is an ordered heterotrimer that is composed of two α1(I) chains and one α2(I) chain encoded by COL1A1 and COL1A2 genes, respectively (Brodsky and Persikov, 2005 ). Previous studies have shown that the missense substitution of glycine can cause the deformation of the triple helix structure of collagen, instability of the helical structure, and an abnormal synthesis of collagen (Brodsky and Persikov, 2005 ; Sun et al, 2015 ; Shi et al, 2019 ). Notably, the replacement of glycine seems to be linked to the degree of clinical severity of OI (Persikov et al, 2004 ; Qiu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The assembly of the three α chains into the monomers of collagen trimeric is greatly influenced by C-propeptides [ 29 ]. Meanwhile, N-linked carbohydrates and intra-chain disulfide bonds stabilize the C-propeptide globular structure.…”
Section: Collagen Type I Synthesismentioning
confidence: 99%